Intervention of University Social Responsibility projects in Mayan communities of Yucatán - Domínguez Castillo, Rodrigo; Aguilar Soberanis, Zulema Noemí (Emerging Trends in Education, 2022)
Contributing and clarifying reality is synonymous with growing and revaluing actions taken within any institution that creates values. The University is one of the social realities that in its productive activity has an inevitable form of impact. Therefore, the purpose of this research was to describe the process of implementation of social responsibility projects of a university subject, linked to the needs of schools in Mayan communities in the eastern part of the State of Yucatán. The approach used in the research was qualitative, using participatory action research as a strategy to implement the projects in four schools, with a total student population of 384 students. Among the main results were that the university students were able to apply the theory seen and analyzed in their classes to a real context, once the main needs in the schools of the Mayan communities were identified. Concluding that in those schools where the projects were implemented, knowledge was socialized so that later the participants could reap the fruits of the work carried out between the university and the community, which is one of the objectives of university social responsibility; achieving with this generate awareness in future generations. Keywords: Education; Social Responsibility; Solidarity commitment; University.